Fluid Balance and Recovery of Native Lung Function in Adult Patients Supported by Venovenous Extracorporeal Membrane Oxygenation and Continuous Renal Replacement Therapy. Issue 6 (August 2019) - McCanny, Peter; Smith, Myles W.; O'Brien, Serena G.; Buscher, Hergen; Carton, Edmund G.
Abstract : Fluid overload is associated with increased mortality in adult patients with acute respiratory distress syndrome. In patients requiring venovenous extracorporeal membrane oxygenation (VV-ECMO), the effects of fluid removal on survival and lung recovery remain undefined. We assessed the impact of early fluid removal in adult patients supported by VV-ECMO and concomitant continuous renal replacement therapy, in an 18-bed tertiary intensive care unit between 2010 and 2015. Twenty-four patients met inclusion criteria, of these 15 (63%) survived to hospital discharge. In our patient group, a more negative cumulative daily fluid balance was strongly associated with improved pulmonary compliance (2.72 ml/cmH2 O per 1 L negative fluid balance; 95% confidence interval [CI]: 1.61–3.83; P < 0.001). In addition, a more negative mean daily fluid balance was associated with improved pulmonary compliance (4.37 ml/cmH2 O per 1 L negative fluid balance; 95% CI: 2.62–6.13; P < 0.001). Survivors were younger and had lower mean daily fluid balance (−0.33 L [95% CI: −1.22 to −0.06] vs. −0.07 L [95% CI: −0.76 to 0.06]; P = 0.438) and lower cumulative fluid balance up to day 14 (−4.60 L [95% CI: −8.40 to −1.45] vs. −1.00 L [95% CI: −4.60 to 0.90]; P = 0.325), although the fluid balance effect alone did not reach statistical significance. Abstract : Supplemental Digital Content is available in the text.